2011
DOI: 10.1136/bmjopen-2011-000234
|View full text |Cite
|
Sign up to set email alerts
|

Self-diagnosis of influenza during a pandemic: a cross-sectional survey

Abstract: BackgroundSelf-diagnosis of influenza is an important component of pandemic control and management as it may support self-management practices and reduce visits to healthcare facilities, thus helping contain viral spread. However, little is known about the accuracy of self-diagnosis of influenza, particularly during pandemics.MethodsWe used cross-sectional survey data to correlate self-diagnosis of influenza with serological evidence of 2009 pandemic influenza A(H1N1) infection (haemagglutination inhibition ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Given the high background rate of respiratory infections, with over 70% of adults reported having experienced an episode in the preceding 12 months, there is not much scope to detect an increase in infections. Furthermore, self-report respiratory infection, particularly influenza, has poor specificity and sensitivity, particularly during times of pandemic virus circulation and subsequent heightened public awareness (Jutel et al , 2011). During the 2009/2010 influenza season in the United States, the main circulating virus was the 2009 pandemic influenza A (H1N1), and very few other seasonal influenza viruses were detected (CDC, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high background rate of respiratory infections, with over 70% of adults reported having experienced an episode in the preceding 12 months, there is not much scope to detect an increase in infections. Furthermore, self-report respiratory infection, particularly influenza, has poor specificity and sensitivity, particularly during times of pandemic virus circulation and subsequent heightened public awareness (Jutel et al , 2011). During the 2009/2010 influenza season in the United States, the main circulating virus was the 2009 pandemic influenza A (H1N1), and very few other seasonal influenza viruses were detected (CDC, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Twitter can be used to assess public knowledge (e.g., the widely held but incorrect assumption that antibiotics will treat a cold, or that a course of antibiotics can be stopped once the symptoms have disappeared) and therefore reveal gaps in public understanding. Also, the problem of inaccuracy of self-diagnosis of influenza due to media hype was illustrated on the swine flu 2009 pandemic by Jutel et al [2011]. Further, attention has turned to Web 2.0 tools other than Twitter.…”
Section: The Role Of Social Network For Risk Communication and News mentioning
confidence: 98%
“…Further, selfdiagnosis is also inaccurate. Jutel, Baker, Stanley, Huang, and Bandaranayake (2011) compared self-ascribed diagnosis with laboratory diagnosis during the 2009 H1N1 pandemic and found that those infected, including health-care workers, were no more likely to self-diagnose accurately than the uninfected. Moreover, influenza is rarely diagnosed by a laboratory test since testing on a large scale places extreme burden upon the health system and testing is often restricted to cases of severe illness and death (Briand, Mounts, & Chamberland, 2011, p. 251).…”
Section: Influenza Public Health and Riskmentioning
confidence: 98%
“…Given that severe symptoms do not necessarily indicate infection (Jutel et al, 2011), Roslyn's beliefs may not reflect actual infection.…”
Section: 'Is This Flu?' Defining and Experiencing Influenza Infectionmentioning
confidence: 99%